Rapid Clinical Induction of Hepatic Cytochrome P4502B6 Activity by Ritonavir - Kharasch, Evan D. (American Society for Microbiology (ASM), 2008)
Ritonavir is the most potent and efficacious inhibitor of cytochrome P4503A (CYP3A), and it is used accordingly for the pharmacoenhancement of other antiretrovirals. Paradoxically, ritonavir induces the clinical metabolism and clearance of many drugs. The mechanism by which ritonavir inhibits and induces clinical drug metabolism is unknown. Ritonavir induces CYP2B6 in human hepatocytes. This investigation tested the hypothesis that ritonavir induces human CYP2B6 in vivo. Thirteen healthy human immunodeficiency virus-negative volunteers underwent a three-way sequential crossover protocol, receiving racemic bupropion after nothing (control), 3 days of treatment with ritonavir, and 2.5 weeks of treatment with ritonavir (400 mg twice a day). Stereoselective bupropion hydroxylation was used as an in vivo probe for CYP2B6 activity. Plasma and urine (R)- and (S)-bupropion and (R,R)- and (S,S)-hydroxybupropion concentrations were measured by liquid chromatography-mass spectrometry. Racemic, (R)-, and (S)-bupropion plasma ratios of the area under the concentration-time curve from 0 h to infinity (AUC(0-)(∞)) (ritonavir/control) were significantly reduced to 0.84, 0.86, and 0.80, respectively, after 3 days of ritonavir treatment and to 0.67, 0.69, and 0.60 after steady-state ritonavir treatment. Apparent oral clearances for racemic, (R)-, and (S)-bupropion all were significantly increased by 1.2-fold after 3 days of ritonavir treatment and by 1.4-, 1.7-, and 1.5-fold after steady-state ritonavir treatment. The plasma (S,S)-hydroxybupropion/(S)-bupropion AUC(0-72) ratio was significantly increased by ritonavir. Formation clearances of both (R,R)- and (S,S)-hydroxybupropion were increased 1.8-fold after 3 days of ritonavir treatment and 2.1-fold after steady-state ritonavir treatment. These results show that ritonavir induces human CYP2B6 activity. Induction is rapid, occurring after only 3 days of ritonavir, and is sustained for at least 2 weeks. The ritonavir induction of CYP2B6 activity may have significant implications for drug interactions and clarify previously unexplained interactions.